Study on Sound Insulation Properties of Different Coated Woven Fabrics (Journal of Fiber Bioengineering and Informatics, 2015)
The aim of this paper is to find the relation between material parameters and insertion loss of different\rfabrics using statistical analysis. This research primarily deals with the sound absorption analysis of\rdifferent uncoated and coated woven textiles fabrics used for curtains as household textiles. The analysis\rof surface morphology was done by scanning electron microscopy to determine the significance of surface\rstructure onto the sound insulation property. The acoustic properties were measured by reverberation\rmethod. The maximum sound insertion loss, minimum sound insertion loss, over all sound insertion loss\rand percentage improvement in sound insertion loss has been discussed and suggested the woven textiles\rto be better sound absorber at higher frequencies. Moreover, the effect structural parameters on average\rsound insulation index were analyzed using SPSS software. The results revealed that warp density, linear\rdensity of warp yarn, thickness are influential parameters for the sound insulation property of uncoated\rfabric whereas the areal density, linear density of warp yarn and thickness influence the sound insulation\rproperty coated fabrics.